BCR–ABL1 transcript doubling time as a predictor for treatment‐free remission failure after imatinib discontinuation in chronic myeloid leukaemia in chronic phase. (8th September 2021) - Kim, Dennis Dong Hwan; Kim, Taehyung Simon; Atenafu, Eshetu G.; Novitzky Basso, Igor; Forrest, Donna; Bence‐Bruckler, Isabelle; Savoie, Lynn; Busque, Lambert; Keating, Mary‐Margaret; Delage, Robert; Xenocostas, Anargyros; Liew, Elena; et al.
Summary: The doubling time (DT) of the BCR–ABL1 quantitative polymerase chain reaction (qPCR) transcript level reflects the re‐growing fraction of leukaemic cells after discontinuation of tyrosine kinase inhibitor (TKI). The present study analyzed monthly DT within six months after imatinib discontinuation in 131 patients. Monthly DT was calculated as x = ln(2)/ K, where x is the DT and K is the fold BCR–ABL1 change from the previous value divided by the number of days between each measurement. The optimal DT value was determined as 12·75 days at two months using a recursive partitioning method. The patients were stratified into three groups: the high‐risk group (DT<12·75 days but >0, with rapidly proliferating chronic myeloid leukaemia (CML) cells; n = 26) showed the lowest molecular relapse‐free survival (mRFS) of 7·7% at 12 months, compared to 53·6% in the intermediate‐risk group (DT≥12·75 days, with slowly proliferating CML cells; n = 16) or 90·0% in the low‐risk group (DT≤0, i.e., without proliferating CML cells; n = 71; P < 0·001). Monthly assessment of DT helps identify high‐risk patients for treatment‐free remission failure with an imminent risk of molecular recurrence, and to define low‐risk patients who can be spared the frequent monitoring of monthly molecular tests.